Educational Leaders as Sherpas: How Leaders’ Actions Promote Collective Teachers' Efficacy - Prelli, Gail E. (Advances in Social Sciences Research Journal, 2018)
Educational leaders continually search for effective practices to improve schools. A quantitative study was conducted to determine what transformative behaviors a leader could use to improve collective teacher efficacy at the level of the entire faculty and at the level of grade level teams. The purpose of this article is to suggest ways a leader could use the inverse relationship between transformational leadership and collective teacher efficacy to create higher levels of collective teacher efficacy in a school as a means to enhance performance. The Collective Efficacy Scale (Goddard, 2001) was modified to measure the perceptions of teachers at both levels; entire faculty’s collective efficacy and the collective efficacy of their team. Thus, this article also provides leaders with important information regarding teaming within schools. The significant difference found between collective teacher efficacy at the level of school and team, provides important information for leaders to consider as they support various professional learning teams. Success for all would be promoted as leaders increase efficacy within teams by employing the concepts of developing leadership teams and purposeful learning communities (Hill & Lundquist, 2008).